Examining the correlations between teacher profiling, ICT skills, and the readiness of integrating augmented reality in education - Azrie, Salleh; Eh Phon, Danakorn Nincarean; Nur Shamsiah, Abdul Rahman; Suhaizal, Hashim; Noor Hidayah, Che Lah (Institute of Electrical and Electronics Engineers Inc., 2023)
This study explores the relationship between respondent demographic profiling and the factors affecting teachers' readiness in adopting augmented reality (AR) for teaching and learning. While AR holds promise for transforming educational practices, the readiness of teachers to adopt this technology remains a critical factor for successful implementation. However, there is a lack of research examining the specific relationship between respondent demographics and the factors influencing teachers' readiness in AR adoption. This study aims to fill this gap by employing a quantitative research approach and survey methodology. By analyzing the data collected from primary school teachers, including demographic information and factors affecting readiness, the study seeks to identify any significant correlations or patterns. The findings will contribute to a better understanding of how respondent demographics influence teachers' readiness in AR integration, addressing a crucial problem in the field of educational technology. The insights gained from this study will inform policymakers and educational institutions in developing targeted strategies to enhance teachers' readiness and support the successful integration of AR in primary school classrooms.